Sense of coherence, mental health, and hair cortisol concentrations among older people during the COVID -19 pandemic: a cross-sectional study - Jenny Koppner; Ann Lindelöf; Fredrik Iredahl; Staffan Nilsson; Annika Thorsell; Hanna Israelsson Larsen; Åshild Faresjö (BMC Public Health, 2024)
Abstract Background A person’s sense of coherence (SoC) is likely to affect coping when exposed to a life changing event like the COVID -19 pandemic, which impacted the older population especially hard, an age group that already suffers from a lot of mental illness. Thus, the aim of this study was to investigate the associations between SoC and mental health in older adults using both screening scales and hair cortisol concentrations (HCC). Method A cross-sectional design studying a cohort of 70–80 years old, N = 260, set in Swedish primary care during the pandemic years 2021–2022. Instruments used are sense of coherence 13 (SoC-13), EQ-5D-3L, Geriatric depression scale 20 (GDS-20), Hospital anxiety and depression scale (HADS), and Perceived stress scale 10 (PSS-10). Sociodemography and factors concerning SoC, and mental health are explored. HCC are measured using radioimmunoassay. Outcome measures are factors independently associated with SoC. Linear regression models were performed with SoC as dependent variable, and priory path analyses explored whether associations with SoC were direct, or indirect via anxiety. Results SoC was significantly associated with anxiety (p < 0.001), perceived economic status (p = 0.003), belief in the future (p = 0.001), and perceived negative mental effect from the COVID -19 pandemic (p = 0.002). The latter was 96% indirectly associated with SoC (p < 0.001), whereas perceived economic status together with belief in the future was 82% directly associated with SoC (p = 0.17). HCC and sex were not significantly associated with SoC, but, noticeably, high HCC was equally distributed between women and men. Women reported significantly lower quality of life (p = 0.03), and more symptoms of anxiety (p = 0.001) and depression (p < 0.001). Conclusion Anxiety, belief in the future, perceived negative effect on mental health due to the pandemic, and perceived economic status were significantly associated with SoC. Anxiety is suggested to be important in explaining the association between perceived negative mental effect from the COVID-19 pandemic and SoC. Women reported significantly poorer mental health and life quality than men.